1997
DOI: 10.1046/j.1365-2559.1997.2660862.x
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathy‐associated T‐cell lymphomas have a cytotoxic T‐cell phenotype

Abstract: EATCL is a clinicopathological entity with a grim prognosis and with tumour cells representing a unique neoplastic equivalent of CTLs arrested in varying stages of activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 10 publications
0
24
0
1
Order By: Relevance
“…26 Cytolytic molecules like granzyme B and perforin are reportedly expressed not only in reactive lymphocytes, but also in neoplastic cells in Hodgkin lymphomas and NHLs as well. 27,28 Granzyme B ϩ tumor cells were mainly found in extranodal T-cell lymphomas and NK cell lymphomas, localized in mucosal lymphoid tissue. 29 It was suggested that these lymphomas are the neoplastic counterparts of activated CTLs or NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…26 Cytolytic molecules like granzyme B and perforin are reportedly expressed not only in reactive lymphocytes, but also in neoplastic cells in Hodgkin lymphomas and NHLs as well. 27,28 Granzyme B ϩ tumor cells were mainly found in extranodal T-cell lymphomas and NK cell lymphomas, localized in mucosal lymphoid tissue. 29 It was suggested that these lymphomas are the neoplastic counterparts of activated CTLs or NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in malignant lymphomas demonstrated that not only reactive cytotoxic leukocytes but also the neoplastic cells in various types of malignant lymphomas expressed these cytotoxic proteins. [12][13][14] Apart from rare NK/T-cell lymphomas, 15,16 expression of granzyme B (GrB), TIA-1, and perforin was noted in 70 to 90% of noncutaneous CD30 ϩ anaplastic large cell lymphomas (ALCL) of T-or null-cell phenotype and in sporadic cases of Hodgkin's disease. [17][18][19] In primary cutaneous lymphomas, recent studies demonstrated expression of GrB and TIA-1 proteins in variable proportions of neoplastic cells in most cases of lymphomatoid papulosis and primary cutaneous CD30 ϩ ALCL, but not or rarely in CD30 Ϫ primary cutaneous large T-cell lymphomas.…”
Section: Granzyme B (Grb) and T-cell-restricted Intracellularmentioning
confidence: 99%
“…1,3). The cells had scant amounts of faintly eosinophilic cytoplasm and large, hyperchromatic nuclei.…”
mentioning
confidence: 99%